Design and Implementation of an Interface Board for a Real-Time Control System Based on the Launch-Xl f28379d Board - Diaz-Diaz, M; Uriarte-Gonzalez, M; Aravena-Carrasco, J (Institute of Electrical and Electronics Engineers Inc., 2021)
Several off-the-shelf real-time control systems are available for industrial and academic applications. These systems enable real-time simulation, rapid control prototyping, and Hardware in the Loop analyses usually intended for power electronics applications. However, despite their easy-to-use environment, most of these systems are very expensive and unflexible, limiting their teaching and academic research usage. Consequently, this paper presents the design and implementation of a low-cost control platform based on the LAUNCH-XL F28379D board from Texas Instruments. An interface board is fully implemented to provide the LAUNCH-XL F28379D board with analogue-to-digital measurements, hardware protections and fibre optic dig-ital outputs. The performance of the proposed control platform is tested in a 20 kVA power converter, providing voltage-current regulation and hardware protection. © 2021 IEEE.